Interactions between posterior gamma and frontal alpha/beta oscillations during imagined actions - De Lange, Floris P.; Jensen, Ole; Bauer, Markus; Toni, Ivan (Frontiers in Human Neuroscience, 2008)
Several studies have revealed that posterior parietal and frontal regions support planning of hand movements but far less is known about how these cortical regions interact during the mental simulation of a movement. Here, we have used magnetoencephalography (MEG) to investigate oscillatory interactions between posterior and frontal areas during the performance of a well-established motor imagery task that evokes motor simulation: mental rotation of hands. Motor imagery induced sustained power suppression in the alpha and beta band over the precentral gyrus and a power increase in the gamma band over bilateral occipito-parietal cortex. During motor imagery of left hand movements, there was stronger alpha and beta band suppression over the right precentral gyrus. The duration of these power changes increased, on a trial-by-trial basis, as a function of the motoric complexity of the imagined actions. Crucially, during a specific period of the movement simulation, the power fluctuations of the frontal beta-band oscillations became coupled with the occipito-parietal gamma-band oscillations. Our results provide novel information about the oscillatory brain activity of posterior and frontal regions. The persistent functional coupling between these regions during task performance emphasizes the importance of sustained interactions between frontal and occipito-parietal areas during mental simulation of action.